AUTONOMOUS LEARNING IN ELT: STUDENTS’ PERCEPTIONS AND PRACTICES - Yuliana Friska (ANGLO-SAXON: Jurnal Ilmiah Program Studi Pendidikan Bahasa Inggris, 2021)
Autonomous learning is considered to be an important tool and is expected to appear in English language learning because it can have a positive impact on the learning process of students. Mainly in the English Language Teaching Department, various studies have been conducted on the views of students and teachers on autonomous learning. However, there is still a lack of investigations on autonomous learning in the context of non-English majors’ students. This research aims to investigate students' perceptions of autonomous learning in English language learning. In addition, the research focuses on exploring students' practice in autonomous learning activities. The questionnaire and semi-structured interview were applied to a randomly selected sample of one hundred forty-nine (149) accounting students. The research findings show that students have a positive attitude towards autonomous learning and the importance of autonomous learning in language learning. Meanwhile, in terms of implementing autonomous learning itself, the students possess low efforts. Therefore, it is recommended that in order to improve the autonomous learning of accounting students of Universitas Pamulang in English teaching and learning, it should be integrated into English teaching and make it an integral part of the EFL curriculum.